Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's break down the solution to each part of the question step-by-step.
### 1. Finding the Solutions of the Equation [tex]\( x^2 - 2x - 4 = -3x + 9 \)[/tex]
To find the solutions, we first set [tex]\( x^2 - 2x - 4 \)[/tex] equal to [tex]\(-3x + 9\)[/tex].
[tex]\[ x^2 - 2x - 4 = -3x + 9 \][/tex]
Rearrange the equation to set it to zero:
[tex]\[ x^2 - 2x - 4 + 3x - 9 = 0 \][/tex]
Combine like terms:
[tex]\[ x^2 + x - 13 = 0 \][/tex]
Now, solve for [tex]\( x \)[/tex] using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = -13 \)[/tex]:
[tex]\[ x = \frac{-1 \pm \sqrt{1^2 - 4(1)(-13)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{1 + 52}}{2} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{53}}{2} \][/tex]
The solutions are:
[tex]\[ x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \][/tex]
So, the solutions are:
[tex]\[ x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \][/tex]
### 2. Finding the [tex]\( y \)[/tex]-coordinates of the [tex]\( y \)[/tex]-intercepts
For [tex]\( y = x^2 - 2x - 4 \)[/tex], set [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 0^2 - 2(0) - 4 = -4 \][/tex]
For [tex]\( y = -3x + 9 \)[/tex], set [tex]\( x = 0 \)[/tex]:
[tex]\[ y = -3(0) + 9 = 9 \][/tex]
So, the [tex]\( y \)[/tex]-coordinates of the y-intercepts are:
[tex]\[ y = -4 \quad \text{and} \quad y = 9 \][/tex]
### 3. Finding the [tex]\( x \)[/tex]-coordinates of the [tex]\( x \)[/tex]-intercepts
For the quadratic [tex]\( y = x^2 - 2x - 4 \)[/tex], set [tex]\( y = 0 \)[/tex]:
[tex]\[ x^2 - 2x - 4 = 0 \][/tex]
Solve for [tex]\( x \)[/tex] using the quadratic formula:
[tex]\[ x = \frac{2 \pm \sqrt{(-2)^2 - 4(1)(-4)}}{2(1)} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{4 + 16}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{20}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm 2\sqrt{5}}{2} \][/tex]
[tex]\[ x = 1 \pm \sqrt{5} \][/tex]
So, the [tex]\( x \)[/tex]-coordinates of the x-intercepts are:
[tex]\[ x = 1 + \sqrt{5} \quad \text{and} \quad x = 1 - \sqrt{5} \][/tex]
For the linear equation [tex]\( y = -3x + 9 \)[/tex], set [tex]\( y = 0 \)[/tex]:
[tex]\[ -3x + 9 = 0 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ -3x = -9 \][/tex]
[tex]\[ x = 3 \][/tex]
So, the [tex]\( x \)[/tex]-coordinate of the x-intercept is:
[tex]\[ x = 3 \][/tex]
### 4. Finding the [tex]\( y \)[/tex]-coordinates of the Intersection Points
To find the [tex]\( y \)[/tex]-coordinates of the intersection points, we already have the [tex]\( x \)[/tex]-coordinates of the intersection points from solving [tex]\( x = \frac{-1 + \sqrt{53}}{2} \)[/tex] and [tex]\( x = \frac{-1 - \sqrt{53}}{2} \)[/tex]:
Substitute these [tex]\( x \)[/tex]-values back into either equation, such as [tex]\( y = x^2 - 2x - 4 \)[/tex].
For [tex]\( x = \frac{-1 + \sqrt{53}}{2} \)[/tex]:
[tex]\[ y = \left( \frac{-1 + \sqrt{53}}{2} \right)^2 - 2\left( \frac{-1 + \sqrt{53}}{2} \right) - 4 \][/tex]
[tex]\[ y \approx -0.420164833920778 \][/tex]
For [tex]\( x = \frac{-1 - \sqrt{53}}{2} \)[/tex]:
[tex]\[ y = \left( \frac{-1 - \sqrt{53}}{2} \right)^2 - 2\left( \frac{-1 - \sqrt{53}}{2} \right) - 4 \][/tex]
[tex]\[ y \approx 21.4201648339208 \][/tex]
So, the approximate [tex]\( y \)[/tex]-coordinates of the intersection points are:
[tex]\[ y \approx -0.420164833920778 \quad \text{and} \quad y \approx 21.4201648339208 \][/tex]
### 5. Finding the [tex]\( x \)[/tex]-coordinates of the Intersection Points
The [tex]\( x \)[/tex]-coordinates of the intersection points are:
[tex]\[ x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \][/tex]
In summary:
- The solutions [tex]\( x \)[/tex]-coordinates: [tex]\( x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \)[/tex].
- The [tex]\( y \)[/tex]-coordinates of the [tex]\( y \)[/tex]-intercepts are [tex]\( -4 \)[/tex] and [tex]\( 9 \)[/tex].
- The [tex]\( x \)[/tex]-coordinates of the [tex]\( x \)[/tex]-intercepts are [tex]\( 1 + \sqrt{5} \)[/tex], [tex]\( 1 - \sqrt{5} \)[/tex], and [tex]\( 3 \)[/tex].
- The [tex]\( y \)[/tex]-coordinates of the intersection points are approximately [tex]\( -0.420164833920778 \)[/tex] and [tex]\( 21.4201648339208 \)[/tex].
- The [tex]\( x \)[/tex]-coordinates of the intersection points are [tex]\( \frac{-1 + \sqrt{53}}{2} \)[/tex] and [tex]\( \frac{-1 - \sqrt{53}}{2} \)[/tex].
### 1. Finding the Solutions of the Equation [tex]\( x^2 - 2x - 4 = -3x + 9 \)[/tex]
To find the solutions, we first set [tex]\( x^2 - 2x - 4 \)[/tex] equal to [tex]\(-3x + 9\)[/tex].
[tex]\[ x^2 - 2x - 4 = -3x + 9 \][/tex]
Rearrange the equation to set it to zero:
[tex]\[ x^2 - 2x - 4 + 3x - 9 = 0 \][/tex]
Combine like terms:
[tex]\[ x^2 + x - 13 = 0 \][/tex]
Now, solve for [tex]\( x \)[/tex] using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = -13 \)[/tex]:
[tex]\[ x = \frac{-1 \pm \sqrt{1^2 - 4(1)(-13)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{1 + 52}}{2} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{53}}{2} \][/tex]
The solutions are:
[tex]\[ x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \][/tex]
So, the solutions are:
[tex]\[ x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \][/tex]
### 2. Finding the [tex]\( y \)[/tex]-coordinates of the [tex]\( y \)[/tex]-intercepts
For [tex]\( y = x^2 - 2x - 4 \)[/tex], set [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 0^2 - 2(0) - 4 = -4 \][/tex]
For [tex]\( y = -3x + 9 \)[/tex], set [tex]\( x = 0 \)[/tex]:
[tex]\[ y = -3(0) + 9 = 9 \][/tex]
So, the [tex]\( y \)[/tex]-coordinates of the y-intercepts are:
[tex]\[ y = -4 \quad \text{and} \quad y = 9 \][/tex]
### 3. Finding the [tex]\( x \)[/tex]-coordinates of the [tex]\( x \)[/tex]-intercepts
For the quadratic [tex]\( y = x^2 - 2x - 4 \)[/tex], set [tex]\( y = 0 \)[/tex]:
[tex]\[ x^2 - 2x - 4 = 0 \][/tex]
Solve for [tex]\( x \)[/tex] using the quadratic formula:
[tex]\[ x = \frac{2 \pm \sqrt{(-2)^2 - 4(1)(-4)}}{2(1)} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{4 + 16}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{20}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm 2\sqrt{5}}{2} \][/tex]
[tex]\[ x = 1 \pm \sqrt{5} \][/tex]
So, the [tex]\( x \)[/tex]-coordinates of the x-intercepts are:
[tex]\[ x = 1 + \sqrt{5} \quad \text{and} \quad x = 1 - \sqrt{5} \][/tex]
For the linear equation [tex]\( y = -3x + 9 \)[/tex], set [tex]\( y = 0 \)[/tex]:
[tex]\[ -3x + 9 = 0 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ -3x = -9 \][/tex]
[tex]\[ x = 3 \][/tex]
So, the [tex]\( x \)[/tex]-coordinate of the x-intercept is:
[tex]\[ x = 3 \][/tex]
### 4. Finding the [tex]\( y \)[/tex]-coordinates of the Intersection Points
To find the [tex]\( y \)[/tex]-coordinates of the intersection points, we already have the [tex]\( x \)[/tex]-coordinates of the intersection points from solving [tex]\( x = \frac{-1 + \sqrt{53}}{2} \)[/tex] and [tex]\( x = \frac{-1 - \sqrt{53}}{2} \)[/tex]:
Substitute these [tex]\( x \)[/tex]-values back into either equation, such as [tex]\( y = x^2 - 2x - 4 \)[/tex].
For [tex]\( x = \frac{-1 + \sqrt{53}}{2} \)[/tex]:
[tex]\[ y = \left( \frac{-1 + \sqrt{53}}{2} \right)^2 - 2\left( \frac{-1 + \sqrt{53}}{2} \right) - 4 \][/tex]
[tex]\[ y \approx -0.420164833920778 \][/tex]
For [tex]\( x = \frac{-1 - \sqrt{53}}{2} \)[/tex]:
[tex]\[ y = \left( \frac{-1 - \sqrt{53}}{2} \right)^2 - 2\left( \frac{-1 - \sqrt{53}}{2} \right) - 4 \][/tex]
[tex]\[ y \approx 21.4201648339208 \][/tex]
So, the approximate [tex]\( y \)[/tex]-coordinates of the intersection points are:
[tex]\[ y \approx -0.420164833920778 \quad \text{and} \quad y \approx 21.4201648339208 \][/tex]
### 5. Finding the [tex]\( x \)[/tex]-coordinates of the Intersection Points
The [tex]\( x \)[/tex]-coordinates of the intersection points are:
[tex]\[ x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \][/tex]
In summary:
- The solutions [tex]\( x \)[/tex]-coordinates: [tex]\( x = \frac{-1 + \sqrt{53}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{53}}{2} \)[/tex].
- The [tex]\( y \)[/tex]-coordinates of the [tex]\( y \)[/tex]-intercepts are [tex]\( -4 \)[/tex] and [tex]\( 9 \)[/tex].
- The [tex]\( x \)[/tex]-coordinates of the [tex]\( x \)[/tex]-intercepts are [tex]\( 1 + \sqrt{5} \)[/tex], [tex]\( 1 - \sqrt{5} \)[/tex], and [tex]\( 3 \)[/tex].
- The [tex]\( y \)[/tex]-coordinates of the intersection points are approximately [tex]\( -0.420164833920778 \)[/tex] and [tex]\( 21.4201648339208 \)[/tex].
- The [tex]\( x \)[/tex]-coordinates of the intersection points are [tex]\( \frac{-1 + \sqrt{53}}{2} \)[/tex] and [tex]\( \frac{-1 - \sqrt{53}}{2} \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.